AFFECT OF SEVERE CHILDHOOD MALTREATMENT ON ANGER CONTROL (SOBER AND USE OF ALCOHOL) AND AGGRESSIVE BEHAVIOR - REHAN , WAIL; ARMIA, REMONDA ESHAYA; ANTFOLK, JAN (Journal of Duhok University, 2023)
Abuse during childhood is an important risk factor for violent behavior and diminished anger management as an adult. The study examined whether participants who reported severe childhood maltreatment also reported high levels of violent conduct and decreased emotional control in sober and drunk states as adults, and compared this to participants who reported less severe maltreatment. We also investigated the link between excessive alcohol consumption and offensive behaviour. The study was based on self-reports of childhood maltreatment, violent conduct, and use of alcohol, in addition to self-reports of the participants' typical levels of anger control in sober and use of alcohol states in a population-based sample (N=10980) of Finnish twins and their siblings. Men with severe emotional abuse reported a higher level of physical violence compared to those with mild emotional abuse. Men who experienced severe emotional abuse reported a higher level of physical violence than those who experienced less severe emotional abuse. In contrast, women with severe physical and emotional abuse and emotional and physical neglect reported higher physical violence levels than women with non-severe levels of these abuse types. Concerning greater levels of verbal violence, men with severe (vs. non-severe) physical abuse reported greater levels of verbal violence. Also, women with severe (vs. non-severe) physical and emotional abuse reported a higher level of verbal violence. In men, there were no effects of severe childhood maltreatment on levels of anger control, neither in the self-reported sober or use of alcohol  state in adulthood. In the self-reported sober state, women who had experienced severe physical violence had higher levels of anger control than in the self-reported use of alcohol  state. In contrast, women who self-reported being sober exhibited reduced levels of anger control when they had experienced severe emotional abuse. In addition, women with severe sexual abuse and severe physical neglect reported higher levels of anger control when sober In their self-reported sober state. Finally, women with severe emotional neglect exhibited reduced levels of anger control. There were substantial links between heavy alcohol consumption and violent behaviour in both men and women. In sum, severe abuse during childhood increases the likelihood of antisocial behaviour and impairs adult anger control